Pendampingan Pengoptimalan Digital Marketing Produk Anyaman Bambu Warga Desa Rogomulyo Kabupaten Semarang - Mohamad Ikhwan Rosyidi; Thohiriyah Thohiriyah; Ruly Indra Darmawan; Rahayu Puji Haryanti; Yuni Dwi Susanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Digital marketing optimization is a society service program done by lecturers and student of the English Department at Universitas Negeri Semarang. The society service is aimed at empowering a local community called Dheling Arts Community in Rogomulyo Village, Semarang Regency to develop their Small and Medium-sized Enterprise (SME) focusing on bamboo working. The community's life (93%) highly depends on traditional farming and bambooworking. In selling and marketing bambooworking products, the community relies on consignment selling and marketing which relatively give small profit. consignment selling and marketing methods are challenged its effectiveness amidst digital development not to mention digital marketing and business. Thus, the empowerment program is performed to give the underlying concept of digital marketing and business so that the SME can reach wider potential buyers using digital marketing tools and platforms. This program was conducted using Participatory Rural Appraisal (PRA) emphasizing the active targeted society involvement. The program resulted in a better understanding of the digital marketing concept. In addition, the local community successfully created a digital marketing media and an e-commerce account to market and sell their products of bamboo working.